Young to Middle-Aged Adults and Low Education: Risk Factors of Spondylitis Tuberculosis with Neurological Deficit and Deformity at Dr. Hasan Sadikin General Hospital - Ismiarto, Adrian F.; Tiksnadi, Bambang; Soenggono, Arifin (Althea Medical Journal, 2018)
Background: Incidence of tuberculosis has risen again, including extrapulmonary tuberculosis. Spondilitis tuberculosis is one the most commonly encountered which can cause disability and even death. The aim of this study was to evaluate characteristics of spondilitis tuberculosis patients and probable risk factors.Methods: This was a descriptive, cross sectional study from all medical records of spondylitis tuberculosis patients at Dr. Hasan Sadikin General Hospital from January 2012 to December 2013. Variables evaluated were demographic data, history related to tuberculosis, nutrinutional status, patientâs characteristics, and treatments received.Results: Spondylitis tuberculosis represented 65.6% of bone and joints tuberculosis.Â  From 78 cases, the male to female ratio was 1.2:1, and mostly found in young and middle-aged adults (79.6%) between 20â64 years old.Â  Patientsâ level of education were mostly elementary school (30.8%) and unemployed.Â  Clinical symptoms were mostly neurological disorders, deformity (kyphotic/gibbus), and tenderness. Predilections sites were thoracal and lumbal vertebrae. Forty eight percents of cases were also sufferring from TB in other organs.Â  Treatments given for these cases were anti tuberculosis drugs (80.8%) and operative procedures (62.8%).Conclusions: Most common clinical manifestations are neurologial deficit, deformity, and tenderness; mostly have pulmonary tuberculosis as a comorbid disease; probable risk factors are young and middle-aged adults, low education level, and unemployment.